FAKTOR-FAKTOR YANG MEMPENGARUHI PERAN SERTA WANITA DALAM MEMENUHI KEBUTUHAN EKONOMI KELUARGA NELAYAN DI DESA BEDONO KECAMATAN SAYUNG KABUPATEN DEMAK - Sutanto, Himawan Arif; Imaningati, Sri (PRESTASI, 2013)
ABSTRACTWomens participation in fulfilling the needs of fishermen fishing families cause rise to the dual role of women fishing, in addition to being a housewife is also required participation in helping the economic needs of the family, on the other hand fisher woman demanded to carry out the main tasks in the household as well as possible. This study aims to (1) identify the profile of womens fishing and (2) determine the factors that affect womens economic needs of fishermen families. A total of 85 female fishers were sampled by purposive sampling. Multiple regression analysis was used to analyze the factors that affect the participation of women in the family economic needs of fishermen. Most of the fishermen in the study area women of childbearing age (55.3%) with relatively low education level of the SD (78.8%). The Number of family members of fishermen in the study are most of the 5-7 people (58.9%) with a average family income (husband plus wife) is 880,000 rupiahs. Factors that significantly influence the role of women in the economic needs of fishermen fishing families is their husbands income, the outpouring of time, level of education, number of family members and fishermen status.Keywords: Gender, multiple roles, women fishermen, socio-economic, fishermen families.